Influence of Heterogeneous Contact Stiffness and Heterogeneous Friction Coefficient on Frictional Squeal - Lijun Zhang; Wenbo Li; Dejian Meng (Shock and Vibration)
Contact stiffness and friction coefficient are excitation sources and key influencing factors to frictional squeal with obvious inhomogeneous characteristic that is always neglected. In this paper, a multipoint contact flexible pin-on-disc system is established considering tangential stiffness. Then influence of contact stiffness and friction coefficient with heterogeneous distribution on frictional squeal is studied using the complex modal analysis. The research shows that contact stiffness and friction coefficient heterogeneities influence the likelihood of occurrence of the squeal, the frequency of the squeal, and the real part of the complex eigenvalue of the system. And when the contact stiffness and friction coefficient are close to the boundary of the region of mode-coupling instability, flexible pin-on-disc system with homogeneous contact stiffness and friction coefficient cannot predict whether frictional squeal occurs or not. Besides, uncertain distribution of contact stiffness and friction coefficient can induce the uncertainty of brake squeal.